Conjugated trapezoidal polymer as well as preparation method and application thereof

By bonding polycyclic aromatic diamines with polycyclic aromatic tetracarboxylic dianhydrides to form conjugated ladder polymers with imide rings, the problem of insufficient proton storage capacity of existing conjugated ladder polymers is solved, and high specific capacity and cycle stability of proton batteries are achieved.

CN121086231APending Publication Date: 2025-12-09NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511320415.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing conjugated ladder polymers have limited active sites and low utilization rates, resulting in insufficient proton storage capacity. Consequently, they exhibit limitations in proton battery anodes, such as insufficient conductivity, low specific capacity, and poor cycle stability.

Method used

A conjugated ladder polymer was prepared by bonding a polycyclic aromatic diamine with a polycyclic aromatic tetracarboxylic dianhydride to form an imide ring. The proton storage capacity was improved by utilizing CN and C=N bonds. Combined with calcination treatment to form a ladder polymer skeleton, rapid interchain charge transport and reversible proton storage were achieved.

Benefits of technology

The prepared conjugated ladder polymer exhibits excellent specific capacity and cycle stability in proton batteries, with a specific capacity of 80 mAh/g at a current density of 10 A/g and a specific capacity retention of 80% after 15,000 cycles, demonstrating high electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005600076880000051
    Figure BDA0005600076880000051
  • Figure BDA0005600076880000061
    Figure BDA0005600076880000061
  • Figure HDA0005600076980000011
    Figure HDA0005600076980000011
Patent Text Reader

Abstract

The invention provides a conjugated trapezoidal polymer as well as a preparation method and application thereof, and belongs to the field of organic polymer synthesis. The conjugated trapezoidal polymer provided by the invention has a structural unit formed by bonding polycyclic aromatic ortho-diamine and polycyclic aromatic hydrocarbon tetracarboxylic dianhydride; two ortho-amino groups in the polycyclic aromatic ortho-diamine and anhydride in the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride form an imide ring through a C-N bond and a C = N bond respectively. The conjugated trapezoidal polymer provided by the invention has a trapezoidal polymer skeleton formed by bonding polycyclic aromatic diamine and polycyclic aromatic hydrocarbon tetracarboxylic dianhydride, and a C = N double bond in an imide ring and a carbonyl group in a polycyclic aromatic hydrocarbon tetracarboxylic dianhydride structural unit endow the conjugated trapezoidal polymer with better proton storage redox kinetics; and highly reversible and rapid water-phase proton storage can be realized. The proton battery formed by the conjugated trapezoidal polymer provided by the invention has excellent specific capacity and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic polymer synthesis, and more particularly to a conjugated ladder polymer, its preparation method, and its applications. Background Technology

[0002] With the rapid development of novel energy storage technologies, high-performance proton batteries have attracted widespread attention due to their environmental friendliness, rapid charge-discharge capability, and high energy density. Conjugated ladder polymers are a class of organic materials with unique geometric structures containing highly conjugated ladder units within their molecules. The rigidity and orderliness of their structure facilitate charge transport and proton diffusion. Compared with traditional linear or random polymers, conjugated ladder polymer materials exhibit superior electronic conductivity, chemical stability, and thermal stability. Furthermore, the functional groups in their structure provide abundant active sites for proton storage and transport.

[0003] However, current conjugated ladder polymers suffer from low proton storage capacity due to a limited number of active sites and low utilization rates. This results in limitations in their application as anodes in proton batteries, including insufficient conductivity, low specific capacity, and poor cycle stability. Therefore, providing a conjugated ladder polymer material with high proton storage capacity, enabling the fabrication of proton batteries with high specific capacity and high cycle stability, has become a pressing technical problem to be solved in this field. Summary of the Invention

[0004] The purpose of this invention is to provide a conjugated ladder polymer, its preparation method, and its applications. The conjugated ladder polymer prepared by the method provided by this invention has excellent proton storage capacity, enabling the prepared proton battery to have excellent specific capacity and high cycle stability.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] The present invention provides a conjugated ladder polymer having a structural unit formed by the bonding of a polycyclic aromatic diamine and a polycyclic aromatic tetracarboxylic dianhydride; wherein the two amino groups at the adjacent positions of the polycyclic aromatic diamine form an imide ring with the anhydride in the polycyclic aromatic tetracarboxylic dianhydride through CN bonds and C=N bonds, respectively.

[0007] Preferably, the polycyclic aromatic diamine comprises 2,3,7,8-tetraaminodibenzo-p-dioxin and / or 2,3,7,8-tetraaminodiphenylcyclodiazanphenanthrene.

[0008] Preferably, the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride includes one or more of pyromellitic dianhydride, naphthalene tetracarboxylic dianhydride, and perylene tetracarboxylic dianhydride.

[0009] The present invention also provides a method for preparing the conjugated ladder polymer described in the above technical solution, comprising the following steps:

[0010] (1) A polycyclic aromatic diamine monomer and a polycyclic aromatic tetracarboxylic dianhydride monomer solution were mixed and subjected to a polycondensation reaction to obtain a precursor.

[0011] (2) The precursor obtained in step (1) is calcined to obtain a conjugated ladder polymer.

[0012] Preferably, in step (1), the molar ratio of the polycyclic aromatic oxo-diamine monomer to the polycyclic aromatic tetracarboxylic dianhydride monomer in the solution is (0.8-1.2):1.

[0013] Preferably, the concentration of the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution in step (1) is 0.05–0.1 mol / L.

[0014] Preferably, the solvent in the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution in step (1) includes N,N-dimethylformamide and / or N-methylpyrrolidone.

[0015] Preferably, the temperature of the polycondensation reaction in step (1) is 150-200°C and the reaction time is 10-12 hours.

[0016] Preferably, the calcination temperature in step (1) is 280–320°C and the calcination time is 7–9 h.

[0017] The present invention also provides the application of the conjugated ladder polymer described in the above technical solution or the conjugated ladder polymer prepared by the preparation method described in the above technical solution in the anode material of proton battery.

[0018] This invention provides a conjugated ladder polymer having a structural unit composed of a polycyclic aromatic 1-oxo diamine and a polycyclic aromatic tetracarboxylic dianhydride. The two amino groups at the adjacent positions of the polycyclic aromatic 1-oxo diamine form an imide ring with the anhydride in the polycyclic aromatic tetracarboxylic dianhydride via CN and C=N bonds, respectively. The conjugated ladder polymer provided by this invention has a ladder polymer backbone composed of a polycyclic aromatic 1-oxo diamine and a polycyclic aromatic tetracarboxylic dianhydride. The two amino groups at the adjacent positions of the polycyclic aromatic 1-oxo diamine form an imide ring with the anhydride in the polycyclic aromatic tetracarboxylic dianhydride via CN and C=N bonds, respectively. The C=N double bond in the imide ring and the carbonyl group in the polycyclic aromatic tetracarboxylic dianhydride structural unit endow the conjugated ladder polymer with better proton storage redox kinetics, enabling rapid interchain charge transport between the extended π-electron delocalization and the highly aromatic ladder polymer backbone, achieving highly reversible and rapid aqueous proton storage. The results of the examples show that the proton half-cell formed by the conjugated ladder polymer provided by the present invention has a specific capacity of 80 mAh / g in an acidic aqueous electrolyte at a current density of 10 A / g, and the specific capacity can reach 80% after 15,000 cycles, exhibiting excellent specific capacity and cycle stability. Attached Figure Description

[0019] Figure 1 The images shown are SEM images of the conjugated ladder polymer prepared in Example 1 of this invention, where (a) is magnified at 50,000 times and (b) is magnified at 8,000 times.

[0020] Figure 2 The infrared spectrum of the conjugated ladder polymer prepared in Example 1 of this invention;

[0021] Figure 3 This is a cyclic voltammetry test diagram of a half-cell in the test example of this invention;

[0022] Figure 4 This is a long-cycle charge-discharge test diagram of the full battery in the test examples of this invention;

[0023] Figure 5 This is a test diagram of the long-cycle charge-discharge test of a half-cell in the test examples of this invention. Detailed Implementation

[0024] The present invention provides a conjugated ladder polymer having a structural unit formed by the bonding of a polycyclic aromatic diamine and a polycyclic aromatic tetracarboxylic dianhydride; wherein the two amino groups at the adjacent positions of the polycyclic aromatic diamine form an imide ring with the anhydride in the polycyclic aromatic tetracarboxylic dianhydride through CN bonds and C=N bonds, respectively.

[0025] In this invention, the polycyclic aromatic diamine preferably includes 2,3,7,8-tetraaminodibenzo-p-dioxin and / or 2,3,7,8-tetraaminodiphenylcyclodiazanphenanthrene, more preferably 2,3,7,8-tetraaminodibenzo-p-dioxin.

[0026] In this invention, the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride preferably includes one or more of pyromellitic tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, and perylene tetracarboxylic dianhydride, and more preferably naphthalene tetracarboxylic dianhydride.

[0027] The present invention limits the types of polycyclic aromatic diamines and polycyclic aromatic tetracarboxylic dianhydrides to the above-mentioned range, which can better obtain conjugated ladder polymers and increase the number of C=N double bonds and carbonyl groups in the conjugated ladder polymers, thereby improving the ability of the conjugated ladder polymers to store protons.

[0028] The conjugated ladder polymer provided by this invention has a ladder polymer skeleton formed by the bonding of a polycyclic aromatic ovoid diamine and a polycyclic aromatic tetracarboxylic dianhydride. In this case, the two amino groups at the adjacent positions of the polycyclic aromatic ovoid diamine form an imide ring with the anhydride in the polycyclic aromatic tetracarboxylic dianhydride through CN and C=N bonds, respectively. The C=N double bond in the imide ring and the carbonyl group in the polycyclic aromatic tetracarboxylic dianhydride structural unit endow the conjugated ladder polymer with better proton storage redox kinetics, enabling rapid interchain charge transport between the extended π electron delocalization and the highly aromatic ladder polymer skeleton, thus achieving highly reversible and rapid aqueous proton storage.

[0029] The present invention also provides a method for preparing the conjugated ladder polymer described in the above technical solution, comprising the following steps:

[0030] (1) A polycyclic aromatic diamine monomer and a polycyclic aromatic tetracarboxylic dianhydride monomer solution were mixed and subjected to a polycondensation reaction to obtain a precursor.

[0031] (2) The precursor obtained in step (1) is calcined to obtain a conjugated ladder polymer.

[0032] In this invention, a polycyclic aromatic diamine monomer and a polycyclic aromatic tetracarboxylic dianhydride monomer solution are mixed and subjected to a polycondensation reaction to obtain a precursor.

[0033] In this invention, the preferred molar ratio of the polycyclic aromatic diamine monomer to the polycyclic aromatic tetracarboxylic dianhydride monomer in the polycyclic aromatic tetracarboxylic dianhydride monomer solution is (0.8–1.2):1, more preferably 1:1. This invention limits the molar ratio of the polycyclic aromatic diamine monomer to the polycyclic aromatic tetracarboxylic dianhydride monomer in the polycyclic aromatic tetracarboxylic dianhydride monomer solution to the above range to ensure that the conjugated ladder polymer simultaneously contains C=N double bonds and carbonyl groups, and further improves the proton storage capacity of the conjugated ladder polymer.

[0034] In this invention, the concentration of the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution is preferably 0.05–0.1 mol / L, more preferably 0.06–0.09 mol / L, further preferably 0.07–0.08 mol / L, and most preferably 0.075 mol / L. Limiting the concentration of the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution to the above range is more conducive to obtaining a homogeneous solution.

[0035] In this invention, the solvent in the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution preferably includes N,N-dimethylformamide and / or N-methylpyrrolidone, more preferably N,N-dimethylformamide. Limiting the solvent to the above-mentioned range allows for better dissolution of the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer.

[0036] In one embodiment of the present invention, the polycondensation reaction can be carried out in a single-necked flask cooling reflux apparatus or a polytetrafluoroethylene (PTFE) reactor. In an embodiment of the present invention, the polycondensation reaction is carried out in a PTFE reactor. Carrying the polycondensation reaction in the above-mentioned apparatus facilitates the formation of polymers with high structural homogeneity during the reaction.

[0037] In this invention, the temperature of the polycondensation reaction is preferably 150–200°C, more preferably 170–190°C, and even more preferably 180°C; the time of the polycondensation reaction is preferably 10–12 h, more preferably 11–12 h. In this invention, the polycondensation reaction can react the diamine in the polycyclic aromatic diamine monomer with the anhydride in the polycyclic aromatic tetracarboxylic dianhydride monomer to obtain an amide bond. Limiting the temperature and time of the polycondensation reaction to the above-mentioned ranges in this invention promotes the full progress of the polycondensation reaction.

[0038] As one embodiment of the present invention, after the polycondensation reaction is completed, the mixed system obtained by the polycondensation reaction can be subjected to solid-liquid separation, and the obtained solid can be washed and dried in sequence to obtain the precursor.

[0039] In one embodiment of the present invention, the mixture is further cooled before solid-liquid separation. The present invention does not specifically limit the cooling rate; it is sufficient to cool the mixture to room temperature.

[0040] In one embodiment of the present invention, the solid-liquid separation method can be vacuum filtration. The present invention does not specifically limit the parameters of the vacuum filtration; parameters commonly used by those skilled in the art can be employed to achieve solid-liquid separation. The present invention obtains solids and liquids through vacuum filtration.

[0041] In one embodiment of the present invention, the solid obtained by vacuum filtration is washed; the washing liquid is, in sequence, a solvent, anhydrous ethanol, and water. In another embodiment, the solvent can be the same as that used in the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution. The present invention does not specifically limit the number of washes with each washing liquid; the number of washes commonly used by those skilled in the art can be employed. The present invention removes unreacted impurities through washing.

[0042] In one embodiment of the present invention, the drying can be vacuum drying; the vacuum drying temperature can be 60°C; and the vacuum drying time can be 12 hours. The present invention does not have special requirements for the vacuum degree of the vacuum drying; parameters commonly used by those skilled in the art can be adopted. The present invention limits the vacuum drying temperature to the above-mentioned range to ensure sufficient drying of moisture.

[0043] After obtaining the precursor, the present invention calcines the precursor to obtain a conjugated ladder polymer.

[0044] In this invention, the calcination is preferably carried out under an argon atmosphere. This invention does not impose any particular limitation on the equipment used for the calcination; any apparatus commonly used by those skilled in the art can be employed.

[0045] In this invention, the calcination temperature is preferably 280–320°C, more preferably 290–310°C, and even more preferably 300°C; the calcination time is preferably 7–9 hours, more preferably 8 hours. This invention allows the precursor to undergo further polycondensation reaction through calcination, yielding a conjugated ladder polymer. The calcination temperature and time affect the degree of polymerization or molecular weight of the product. Limiting the calcination temperature and time to the above-mentioned ranges in this invention is more conducive to the polycondensation reaction, resulting in a conjugated ladder polymer with a suitable degree of polymerization and molecular weight.

[0046] As one embodiment of the present invention, taking 2,3,7,8-tetraaminodibenzo-p-dioxin as the polycyclic aromatic diamine monomer and naphthalene tetracarboxylic dianhydride as the polycyclic aromatic tetracarboxylic dianhydride monomer as an example, the chemical reaction formula in the preparation process is shown in Formula 1:

[0047]

[0048] Where n is an integer between 350 and 400.

[0049] This invention utilizes the condensation reaction between the diamine in the polycyclic aromatic diamine monomer and the anhydride in the polycyclic aromatic tetracarboxylic dianhydride monomer to obtain amide bonds. Further condensation reaction is carried out after calcination to obtain an imide ring, resulting in a polymer rich in C=N double bonds. Due to the presence of the polycyclic aromatic tetracarboxylic dianhydride monomer, a certain amount of carbonyl groups are retained in the polymer. The presence of C=N double bonds and carbonyl groups endows the conjugated ladder polymer with better proton storage redox kinetics, enabling rapid interchain charge transport between the extended π electron delocalization and the highly aromatic ladder polymer backbone, thus achieving highly reversible and rapid aqueous phase proton storage.

[0050] The present invention also provides the application of the conjugated ladder polymer described in the above technical solution or the conjugated ladder polymer prepared by the preparation method described in the above technical solution in the anode material of proton battery.

[0051] As one embodiment of the present invention, the proton battery negative electrode material includes a substrate and a negative electrode material coated on the substrate, wherein the negative electrode material includes the conjugated ladder polymer, conductive agent and binder described in the above technical solution.

[0052] In one embodiment of the present invention, the areal density of the conjugated ladder polymer in the negative electrode of the proton battery on the substrate can be 1 to 1.5 mg / cm³. 2 The present invention limits the areal density of the conjugated ladder polymer on the substrate in the proton battery negative electrode to the range mentioned above, which can help improve the performance of the proton battery.

[0053] The present invention does not have any particular limitation on the types of conductive agent, binder and substrate, and can use conductive agent, binder and substrate commonly used by those skilled in the art to prepare proton battery anode materials.

[0054] The present invention does not impose any special limitation on the ratio of the conjugated ladder polymer, conductive agent and binder. The ratio commonly used by those skilled in the art to prepare proton batteries can be used to meet the above-mentioned areal density.

[0055] The present invention does not impose any particular limitation on the preparation method of the proton battery anode material; the anode material with the above composition can be obtained by means commonly used by those skilled in the art.

[0056] In one embodiment of the present invention, the proton battery negative electrode can be matched with a vanadium iron Prussian blue positive electrode to form a proton battery.

[0057] In this invention, the PN ratio (mass ratio of positive electrode to negative electrode active material) in the proton battery is preferably 1:1.

[0058] In this invention, the electrolyte in the proton battery can be 0.5-1M H2SO4 or 8-9.5M H3PO4.

[0059] This invention does not impose any special limitations on the selection of other unmentioned components in the proton battery; commonly used proton battery components by those skilled in the art can be used.

[0060] The present invention does not impose any special limitations on the assembly method of the proton battery; assembly can be carried out using assembly methods commonly used by those skilled in the art.

[0061] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0062] Example 1

[0063] A conjugated ladder polymer has the following structural formula:

[0064]

[0065] Where n is an integer between 350 and 400;

[0066] The preparation method is as follows:

[0067] (1) 2,3,7,8-Tetraaminodibenzo-p-dioxin and naphthalene tetracarboxylic dianhydride solution (solvent is N,N-dimethylformamide, concentration is 0.075mol / L) were mixed in a polytetrafluoroethylene reactor and subjected to polycondensation reaction at 180℃ for 12h. After the polycondensation reaction was completed, the mixture was cooled to room temperature and filtered to separate the solid and liquid. The obtained solid was washed with N,N-dimethylformamide, ethanol and water in sequence, and finally vacuum dried at 60℃ for 12h to obtain the precursor. The molar ratio of 2,3,7,8-tetraaminodibenzo-p-dioxin to naphthalene tetracarboxylic dianhydride in the solution was 1:1.

[0068] (2) The precursor obtained in step (1) is calcined at 300°C for 8 hours under an argon atmosphere to obtain a conjugated ladder polymer.

[0069] The conjugated ladder polymer obtained in Example 1 was tested using scanning electron microscopy, and the SEM images are shown below. Figure 1 As shown, the left image is magnified 50,000 times, and the right image is magnified 8,000 times. Figure 1 It can be seen that the conjugated ladder polymer exhibits a layered polymer structure and has weak crystallinity.

[0070] The conjugated ladder polymer prepared in Example 1 was tested using an infrared spectrometer, and the resulting infrared spectrum is shown below. Figure 2 As shown, from Figure 2 The wave number can be observed to be 1750 cm⁻¹ -1 The peak corresponds to the stretching vibration of the carbonyl group, with a wavenumber of 1350 cm⁻¹. -1 The peak corresponds to the stretching vibration of the imine bond, indicating that the conjugated ladder polymer contains carbonyl and imine bonds (C=N double bonds).

[0071] Application examples

[0072] A method for preparing a proton battery anode material:

[0073] The conjugated ladder polymer prepared in Example 1 was dispersed in N-methylpyrrolidone (NMP) solvent at a mass ratio of 7:2:1 with conductive agent Ketjen black and binder polyvinylidene fluoride (PVDF). The mixture was ground into a slurry (the total mass ratio of the conjugated ladder polymer, Ketjen black, and PVDF liquid to the volume ratio of N-methylpyrrolidone was 1 g:10 mL). This slurry was then uniformly coated onto a substrate (carbon paper), with the mass-to-area ratio of the conjugated ladder polymer on the substrate being 1 mg / cm². 2 The proton battery negative electrode is obtained by vacuum drying at 60°C for 12 hours and then cutting it into round pieces with a diameter of 5mm using a cutting machine.

[0074] Test case

[0075] (1) Half-cell test

[0076] Preparation of activated carbon counter electrode: Take 1.6g activated carbon (YP80F), 0.2g acetylene black, and 0.2g polytetrafluoroethylene powder (PTFE) and place them in a beaker. Add 50mL isopropanol and stir magnetically for 2 hours. Disperse by ultrasonic separation for 1 hour. Place the solution in a forced-air oven and dry until viscous. Add a small amount of isopropanol, place it on weighing paper, brush it flat with a scraper, and cut it into 5mm diameter round pieces with a cutting machine to obtain the activated carbon counter electrode. The electrolyte is 9.5M H3PO4.

[0077] (2) Full battery test

[0078] The positive electrode of the proton battery uses vanadium iron Prussian blue, which is dispersed with conductive agent Ketjen black and binder polyvinylidene fluoride (PVDF) in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 6:3:1. After being ground into a slurry, it is uniformly coated onto a substrate (carbon paper). The mass ratio of solid to solvent is 1:5, and the mass area ratio of vanadium iron Prussian blue active material on the substrate is 1 mg / cm². 2 The proton battery positive electrode was obtained by vacuum drying at 60°C for 12 hours and then cutting it into round pieces with a diameter of 5mm using a cutting machine.

[0079] The positive and negative electrode active mass PN ratio is 1:1, the separator is Whatman filter paper cut into 6mm diameter discs, and the electrolyte is 9.5M H3PO4, forming a Swagelok battery.

[0080] The assembled half-cells and full-cells were placed on the Land CT2001A battery testing system for electrochemical performance testing. The test temperature was 25℃, the half-cell voltage range was -0.6 to 0.6V, and the full-cell voltage range was 0 to 1.3V.

[0081] Cyclic voltammetry test results of half-cell at different scan rates are shown in the figure. Figure 3 As shown, from Figure 3 It can be seen that the redox peaks of the conjugated ladder polymer are located near -0.15V and 0.15V, which have lower potentials and can yield higher energy densities.

[0082] The long-cycle charge-discharge test diagram of the full battery is shown below. Figure 4 As shown, from Figure 4 The results show that the initial specific capacity is about 28 mAh / g, and after 7000 long cycles, the specific capacity can still reach about 24 mAh / g, with only about 15% decay.

[0083] The long-cycle charge-discharge test diagram of the half-cell is shown below. Figure 5 As shown, from Figure 5 As can be seen, in acidic aqueous electrolyte, the half-cell formed by the conjugated ladder polymer material has a specific capacity of 80 mAh / g at a current density of 10 A / g, and the specific capacity can reach 80% of the initial specific capacity after 15,000 cycles, exhibiting excellent specific capacity and cycle stability.

[0084] The proton half-cell formed by the conjugated ladder polymer provided by this invention has a specific capacity of 80 mAh / g in an acidic aqueous electrolyte at a current density of 10 A / g, and the specific capacity can reach 80% after 15,000 cycles, exhibiting excellent specific capacity and cycle stability.

[0085] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A conjugated ladder polymer having a structural unit formed by the bonding of a polycyclic aromatic diamine and a polycyclic aromatic tetracarboxylic dianhydride; wherein the two amino groups at the adjacent positions of the polycyclic aromatic diamine form an imide ring with the anhydride in the polycyclic aromatic tetracarboxylic dianhydride through CN and C=N bonds, respectively.

2. The conjugated ladder polymer according to claim 1, characterized in that, The polycyclic aromatic diamines include 2,3,7,8-tetraaminodibenzo-p-dioxin and / or 2,3,7,8-tetraaminodiphenylcyclodiazanphenanthrene.

3. The conjugated ladder polymer according to claim 1, characterized in that, The polycyclic aromatic hydrocarbon tetracarboxylic dianhydride includes one or more of pyromellitic dianhydride, naphthalenetetracarboxylic dianhydride, and perylenetetracarboxylic dianhydride.

4. A method for preparing the conjugated ladder polymer according to any one of claims 1 to 3, comprising the following steps: (1) A polycyclic aromatic diamine monomer and a polycyclic aromatic tetracarboxylic dianhydride monomer solution were mixed and subjected to a polycondensation reaction to obtain a precursor. (2) The precursor obtained in step (1) is calcined to obtain a conjugated ladder polymer.

5. The preparation method according to claim 4, characterized in that, In step (1), the molar ratio of the polycyclic aromatic diamine monomer to the polycyclic aromatic tetracarboxylic dianhydride monomer in the solution is (0.8-1.2):

1.

6. The preparation method according to claim 4 or 5, characterized in that, In step (1), the concentration of the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution is 0.05–0.1 mol / L.

7. The preparation method according to claim 6, characterized in that, The solvent in the polycyclic aromatic hydrocarbon tetracarboxylic dianhydride monomer solution in step (1) includes N,N-dimethylformamide and / or N-methylpyrrolidone.

8. The preparation method according to claim 4, characterized in that, The temperature of the polycondensation reaction in step (1) is 150-200℃, and the reaction time is 10-12h.

9. The preparation method according to claim 4, characterized in that, The calcination temperature in step (1) is 280–320°C, and the calcination time is 7–9 h.

10. The application of the conjugated ladder polymer according to any one of claims 1 to 3 or the conjugated ladder polymer prepared by the preparation method according to any one of claims 4 to 9 in the anode material of proton batteries.